Conjugate observations of electromagnetic ion cyclotron waves associated with traveling convection vortex events. Issue 7 (17th July 2017) - Kim, Hyomin; Clauer, C. Robert; Gerrard, Andrew J.; Engebretson, Mark J.; Hartinger, Michael D.; Lessard, Marc R.; Matzka, Jürgen; Sibeck, David G.; Singer, Howard J.; Stolle, Claudia; Weimer, Daniel R.; Xu, Zhonghua
Abstract: We report on simultaneous observations of electromagnetic ion cyclotron (EMIC) waves associated with traveling convection vortex (TCV) events caused by transient solar wind dynamic pressure ( P d ) impulse events. The Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft located near the magnetopause observed radial fluctuations of the magnetopause, and the GOES spacecraft measured sudden compressions of the magnetosphere in response to sudden increases in P d . During the transient events, EMIC waves were observed by interhemispheric conjugate ground‐based magnetometer arrays as well as the GOES spacecraft. The spectral structures of the waves appear to be well correlated with the fluctuating motion of the magnetopause, showing compression‐associated wave generation. In addition, the wave features are remarkably similar in conjugate hemispheres in terms of bandwidth, quasiperiodic wave power modulation, and polarization. Proton precipitation was also observed by the DMSP spacecraft during the wave events, from which the wave source region is estimated to be 72°–74° in magnetic latitude, consistent with the TCV center. The confluence of space‐borne and ground instruments including the interhemispheric, high‐latitude, fluxgate/induction coil magnetometer array allows us to constrain the EMIC source region while also confirming the relationship between EMIC waves and the TCV current system. Key Points: EMIC waves were observed by interhemispheric magnetometer arrays in association with transient solar wind pressure changes and TCVs The waves are well correlated with fluctuating motion of the magnetopause, suggesting compression‐associated wave generation The multipoint observations show wave events over an extensive latitudinal ( L = 6–10) and longitudinal (6 h in MLT) range